2018
DOI: 10.1111/scd.12290
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis VI and effects on growth of the apical bases: a case report

Abstract: By understanding the craniofacial growth changes in MPS VI patients, new treatment options may be developed for affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…These studies showed that MPS patients can manifest with a tendency towards vertical growth of their face resulting in a dolichocephalic facial pattern (a relatively long face). 33 , 34 A high‐arched palate and a narrow maxilla have been found as well. Turra et al, 35 found a high‐arched palate in 71.2% ( n = 47) of MPS patients in a cross‐sectional study, but this study was not included in our database, because the MPS type was not specified.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These studies showed that MPS patients can manifest with a tendency towards vertical growth of their face resulting in a dolichocephalic facial pattern (a relatively long face). 33 , 34 A high‐arched palate and a narrow maxilla have been found as well. Turra et al, 35 found a high‐arched palate in 71.2% ( n = 47) of MPS patients in a cross‐sectional study, but this study was not included in our database, because the MPS type was not specified.…”
Section: Discussionmentioning
confidence: 84%
“…Two studies presented results of cephalometric characteristics of MPS I ( n = 1), MPS IV ( n = 8), and MPS VI ( n = 9) patients. These studies showed that MPS patients can manifest with a tendency towards vertical growth of their face resulting in a dolichocephalic facial pattern (a relatively long face) 33,34 . A high‐arched palate and a narrow maxilla have been found as well.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…La electroforesis bidimensional de mucopolisacaridosis en muestra de orina mostró un gran aumento de dermatán sulfato, lo que sugiere mucopolisacaridosis tipo VI. La deficiencia enzimática de la arilsulfatasa B fue identificada por ensayo de enzima ASB 9 de los fibroblastos cultivados de la paciente, la actividad de ABS fue 120 y el rango control de 300 a 900 nmol/h/mg.…”
Section: Reporte De Casounclassified